Pruning management of cassava for animal feeding: parameters of the root - Curcelli, Felipe [UNESP]; Bicudo, Silvio Jose [UNESP]; Aguiar, Eduardo Barreto [UNESP]; Valdivié, Manoel Isidoro (My University, 2014)
To evaluate the effects of pruning at different data on the parameters of the root, a randomized complete block experiment involving the IAC-14 cassava variety was conducted between years 2008/2010, at UNESP, Botucatu, Brazil. Plants were pruned monthly from the 7th to the 15th month after planted. The chemical analyses were performed at the time of harvest, that is, 22 months after planting (MAP). Production and yield plus the starch, crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF), total digestible nutrients (TDN), nitrogen-free extract percentage (NFE) and total sugars (TS) contents of the root were analyzed. Pruning shoots of IAC-14 variety before the physiological rest affects positively yield and the percentage of root, and do not affect the root starch content.
Keywords: Food science; Starch; Fiber; Ruminant; Monogastric